How many species are there in the monocot order Petrosaviales? Synonymization of Petrosavia amamiensis with P. sakuraii - Nuraliev, Maxim S.; Sokoloff, Dmitry D.; Averyanov, Leonid V.; Remizowa, Margarita V. (Phytotaxa, 2022)
A reassessment of taxonomy and geographical distribution of a widespread Asian mycoheterotrophic species Petrosavia sakuraii is presented. Petrosavia amamiensis recently described from the Japanese Ryukyu Islands is demonstrated to fit closely the morphological diversity of P. sakuraii. Data from geography, molecular phylogenetics and reproductive biology also provide no substantial evidences in favor of consideration of the specimens of Petrosavia from Ryukyu as a distinct species. Accordingly, P. amamiensis is here reduced to a taxonomic synonym of P. sakuraii. Worldwide distribution range of P. sakuraii is reviewed to summarize the scattered evidences accumulated to date in the forms of herbarium specimens and publications of range extensions. A disjunct distribution pattern is highlighted between the populations in Sumatra and the rest of the species range: P. sakuraii occurs from the Himalayas to the Honshu Island, but within the Indochinese Peninsula it is known only in its northernmost part. Finally, typification of P. sakuraii and its synonym P. sinii is revised, and lectotypes are designated for both names.